Politicians on the boards of firm directors in the MENA countries: Do connections affect confidence in business sales? - Hassan F. Gholipour; Mohammad Reza Farzanegan (Philipps-University Marburg, School of Business and Economics, 2024)
This study examines the relationship between firms' political connections and their confidence in achieving enhanced future sales. Using firm-level survey data from selected Middle Eastern and North African (MENA) countries, we apply ordered probit regressions to demonstrate that businesses with board members who have political experience in government show increased confidence in anticipating improved sales. This positive association remains robust even after controlling for various determinants of managers' sentiment. Quantitatively, our results indicate that having a politician on the board increases the predicted probability of a positive change in firm sales expectations by approximately 10 percentage points, while also reducing the predicted probability of no change or a decrease in sales expectations. Furthermore, we identify that membership in business associations serves as an important mediator, facilitating access to information, markets, credit, and lobbying opportunities. The findings also highlight the significance of a well-defined business strategy and firm size as key factors mediating the relationship between firms' political connections and their confidence in future sales.
Keywords: 330; Business confidence; Middle East; Political connection; Sentiment; Survey Data